2018
DOI: 10.5455/faa.285704
|View full text |Cite
|
Sign up to set email alerts
|

Integrated approaches for controlling purple blotch of onion for true seed production in Faridpur of Bangladesh

Abstract: water each + Sanitation, T 5 = Trichoderma harzianum compost used during final land preparation @ 50 g m −2 plot + T 3 , T 6 = Trichoderma harzianum compost used during final land preparation + Trichoderma harzianum 3 times spray @ 50 ml L −1 water + Sanitation, T 7 = Difenoconazole 2 times @ 1 ml L −1 water + combination of Iprodione and Mancozeb with Metalaxyl 2 times spray @ 2 g L −1 water each and T 8 = Control. Successful control of purple blotch of onion was achieved by spraying fungicide (chemical plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Ali et al, (2015) recorded that seed yield of onion in the ranged of 370 -500 Kg/ha. Ahmed et al, (2018) reported highest onion seed yield i.e 580 kg/ha against purple blotch of onion. Zakirul islam (2013) observed maximum seed yield (649.40 kg/ha) with low incidence and intensity of purple blotch of onion.…”
Section: Effect Of Different Chemical Treatments On Seed Yield Of Onionmentioning
confidence: 96%
“…Ali et al, (2015) recorded that seed yield of onion in the ranged of 370 -500 Kg/ha. Ahmed et al, (2018) reported highest onion seed yield i.e 580 kg/ha against purple blotch of onion. Zakirul islam (2013) observed maximum seed yield (649.40 kg/ha) with low incidence and intensity of purple blotch of onion.…”
Section: Effect Of Different Chemical Treatments On Seed Yield Of Onionmentioning
confidence: 96%
“…Meanwhile, cultural practices, including crop rotation, field sanitation, intercropping, optimal spacing, good drainage, and the utilization of resistant varieties like Red Star F 1 , Red Pinoy F 1 , and Red Passion F 1 , have demonstrated effectiveness in manag-ing purple blotch disease (Ahmed et al, 2018;MOA, 2019).…”
Section: Original Research Articlementioning
confidence: 99%